(untitled) (Revista Contexto & Educação, 2023)
This article brings to light questions that demonstrate to focus on the factors that contribute to the evasion in ICT courses - Information and Communication Technology, influencing the work of professionals in the segment. Between 2010 and 2019, research by the agencies presented in this study, which has been monitoring the segment, reveals a constant demand for human resources for the sector in Brazil. The factors that contribute to the perennial scenario of lack of qualified ICT professionals in the last decades, indicate that it is related to student dropout in these courses. The diagnosis of this research, with a qualitative approach, was obtained through a bibliographic research and a documentary exploration in academic digital libraries and agencies of the segment, complemented with an analysis of student evasion in the last years in two academic institutions in Minas Gerais. The observed results demonstrate that student dropout in Computer Engineering courses and other analyzed correlates has a strong inclination towards the basically technical training model aimed at meeting the labor market and legal and professional issues in the segment that collaborate with the scarcity of professionals due student evasion in these courses, creating a lack of human resources for the segment in the state of Minas Gerais and Brazil.